The Application of Blockchain Technology in Stock Trading Efficiency - Vidya Ramadhan Putra Pratama (Nomico, 2025)
Indonesia’s stock market has grown rapidly in volume and retail participation, creating increasing pressure on market infrastructures to deliver faster, more transparent, and more secure end-to-end processes. This study examines the potential of blockchain technology to enhance the efficiency of stock trading processes, covering trade execution at the Indonesia Stock Exchange, clearing performed by the Indonesia Clearing and Guarantee Corporation, and settlement and asset recording conducted by the Indonesian Central Securities Depository. Using a systematic literature review, the study synthesizes evidence from reputable academic databases and institutional publications through a structured selection approach and critical appraisal. The findings indicate that blockchain introduces substantial opportunities to accelerate transaction processing, strengthen data integrity, streamline clearing workflows, enable near real-time settlement, and automate corporate actions through smart contracts. Nevertheless, the study also reveals significant challenges, including limitations in scalability, infrastructure investment requirements, regulatory gaps, governance complexity, and the need for high-level technical readiness among market institutions. The study concludes that blockchain can serve as a transformative infrastructure for Indonesia’s capital market, provided its implementation follows a phased approach supported by rigorous pilot testing and clear regulatory frameworks.